HUBUNGAN STATUS GIZI DENGAN PERKEMBANGAN BALITA 24–36 BULAN - Indah Permatasari; Nurul Madina (Jurnal Keperawatan Widya Gantari Indonesia, 2026)
Nutritional status is an indication of how well the body uses and absorbs nutrients to meet its needs. Malnutrition will cause growth retardation in children. The objective of this study was to determine the relationship between nutritional status and the development of children aged 24-36 months in the working area of the Jatijajar Community Health Center in Depok City. This study is a quantitative study with a cross-sectional approach. The sample size was 86 respondents using purposive sampling. Data collection was conducted through interviews using the Developmental Screening Questionnaire (KPSP) and nutritional status measurements. The results of this study show that children with normal nutritional status, which is the majority of children (76.7% or 66 respondents), have appropriate development, while children with thin nutritional status, which is the majority of children (5.8% or 5 respondents), have questionable development. The Spearman rank correlation test results obtained a P-value of 0.009, which means that Ha is accepted. This study concluded that there is a significant relationship between nutritional status and the development of children aged 24-36 months in the working area of the Jatijajar Community Health Center in Depok City. Health institutions can provide monthly training programs for health workers on child development stimulation, hold educational programs for new parents on the importance of healthy eating patterns, and conduct monthly nutritional status checks.